Nutritional status and nutrition risk screening in hospitalized children in New Zealand. (3rd June 2013) - Moeeni, Vesal; Walls, Tony; Day, Andrew S
Abstract: Aim: Children requiring hospitalization are at risk of malnutrition. This study aimed to define the nutritional status of paediatric inpatients in comparison with healthy children and to compare and contrast the feasibility and validity of three nutritional risk screening (NRS) tools in the hospitalized children. Methods: A total of 162 children admitted to Christchurch Hospital were assessed along with a similar group of healthy children. Their nutritional state was assessed and classified using standard criteria. The NRS tools were applied, and patients were classified into low‐, medium‐ and high‐risk groups. The feasibility and validity of the tools were assessed. Results: Under‐nutrition was more frequent in the inpatient group (9.9% vs. 3.7%; p = 0.04), whereas both groups had similar rates of overweight/obesity. NRS tools were able to identify between 81% and 100% of the malnourished patients in the medium‐ to high‐risk groups. Undernourished patients had longer hospital stay than well‐nourished patients. Conclusion: Hospitalized children have higher rates of under‐nutrition than healthy children in NZ. The three NRS tools were able to identify children at nutritional risk with differing utility. In this setting, STRONGkids was the most reliable tool.